# |
ODE |
CAS classification |
Solved? |
time (sec) |
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{-x}\right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
1.753 |
|
\[
{}y^{\prime \prime }+y = \sec \left (x \right )^{3}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
2.219 |
|
\[
{}y^{\prime \prime }-y = \frac {1}{\sqrt {1-{\mathrm e}^{2 x}}}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
1.991 |
|
\[
{}y^{\prime \prime }-y = {\mathrm e}^{-2 x} \sin \left ({\mathrm e}^{-x}\right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
2.217 |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 15 \,{\mathrm e}^{-x} \sqrt {x +1}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
1.555 |
|
\[
{}y^{\prime \prime }+4 y = 2 \tan \left (x \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
4.732 |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{2 x}}{\left ({\mathrm e}^{x}+1\right )^{2}}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.931 |
|
\[
{}y^{\prime \prime }+y^{\prime } = \frac {1}{{\mathrm e}^{x}+1}
\] |
[[_2nd_order, _missing_y]] |
✓ |
2.266 |
|
\[
{}x^{2} y^{\prime \prime }-y^{\prime } x +y = \ln \left (x \right )
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
1.857 |
|
\[
{}x^{2} y^{\prime \prime }+3 y^{\prime } x +5 y = \frac {5 \ln \left (x \right )}{x^{2}}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
18.487 |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-y^{\prime } x +y = 9 x^{2} \ln \left (x \right )
\] |
[[_3rd_order, _exact, _linear, _nonhomogeneous]] |
✓ |
0.285 |
|
\[
{}\left (x -2\right )^{2} y^{\prime \prime }-3 \left (x -2\right ) y^{\prime }+4 y = x
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
1.450 |
|
\[
{}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }+y^{\prime } x -y = x^{2}
\] |
[[_3rd_order, _with_linear_symmetries]] |
✓ |
1.308 |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+3 y = 60 \cos \left (3 t \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.428 |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 9 \,{\mathrm e}^{-2 t}
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
0.276 |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 2 t^{2}+1
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
0.287 |
|
\[
{}y^{\prime \prime }+4 y = 8 \sin \left (2 t \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.345 |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 4 \,{\mathrm e}^{-t}+2 \,{\mathrm e}^{t}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.283 |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 8 \,{\mathrm e}^{-t} \sin \left (t \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.448 |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 8 \,{\mathrm e}^{t} \sin \left (2 t \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.339 |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 54 t \,{\mathrm e}^{-2 t}
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.280 |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 9 \,{\mathrm e}^{2 t} \operatorname {Heaviside}\left (t -1\right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.598 |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 2 \sin \left (t \right ) \operatorname {Heaviside}\left (t -\pi \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.710 |
|
\[
{}y^{\prime \prime }+4 y = 8 \sin \left (2 t \right ) \operatorname {Heaviside}\left (t -\pi \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.579 |
|
\[
{}y^{\prime \prime }+4 y = 8 \left (t^{2}+t -1\right ) \operatorname {Heaviside}\left (t -2\right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
1.184 |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{t} \operatorname {Heaviside}\left (t -2\right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.557 |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = \delta \left (t -2\right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.549 |
|
\[
{}y^{\prime \prime }+4 y = 4 \operatorname {Heaviside}\left (t -\pi \right )+2 \delta \left (t -\pi \right )
\] |
[[_2nd_order, _linear, _nonhomogeneous]] |
✓ |
0.800 |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+4 y^{\prime }-4 y = 10 \,{\mathrm e}^{-t}
\] |
[[_3rd_order, _with_linear_symmetries]] |
✓ |
0.436 |
|
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = 120 \,{\mathrm e}^{3 t} \operatorname {Heaviside}\left (t -1\right )
\] |
[[_high_order, _linear, _nonhomogeneous]] |
✓ |
7.908 |
|
\[
{}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-4 y = 40 t^{2} \operatorname {Heaviside}\left (t -2\right )
\] |
[[_high_order, _linear, _nonhomogeneous]] |
✓ |
8.227 |
|
\[
{}y^{\prime \prime \prime \prime }+4 y = \left (2 t^{2}+t +1\right ) \delta \left (t -1\right )
\] |
[[_high_order, _linear, _nonhomogeneous]] |
✓ |
3.254 |
|
\[
{}\left [\begin {array}{c} x^{\prime }+2 x-y=0 \\ x+y^{\prime }-2 y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.536 |
|
\[
{}\left [\begin {array}{c} 2 x^{\prime }+x-5 y^{\prime }-4 y=0 \\ -y^{\prime }-2 x+y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.443 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-x+3 y=0 \\ 3 x-y^{\prime }+y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.467 |
|
\[
{}\left [\begin {array}{c} x^{\prime \prime }+x^{\prime }+y^{\prime }-2 y=0 \\ x^{\prime }+x-y^{\prime }=0 \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.056 |
|
\[
{}\left [\begin {array}{c} x^{\prime \prime }-3 x-4 y=0 \\ x+y^{\prime \prime }+y=0 \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.055 |
|
\[
{}\left [\begin {array}{c} y_{1}^{\prime }-y_{2}=0 \\ 4 y_{1}+y_{2}^{\prime }-4 y_{2}-2 y_{3}=0 \\ -2 y_{1}+y_{2}+y_{3}^{\prime }+y_{3}=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.487 |
|
\[
{}\left [\begin {array}{c} y_{1}^{\prime }-2 y_{1}+3 y_{2}-3 y_{3}=0 \\ -4 y_{1}+y_{2}^{\prime }+5 y_{2}-3 y_{3}=0 \\ -4 y_{1}+4 y_{2}+y_{3}^{\prime }-2 y_{3}=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.466 |
|
\[
{}\left [\begin {array}{c} x^{\prime }+x+2 y=8 \\ 2 x+y^{\prime }-2 y=2 \,{\mathrm e}^{-t}-8 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.530 |
|
\[
{}\left [\begin {array}{c} x^{\prime }=2 x-3 y+t \,{\mathrm e}^{-t} \\ y^{\prime }=2 x-3 y+{\mathrm e}^{-t} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.502 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-x-2 y={\mathrm e}^{t} \\ -4 x+y^{\prime }-3 y=1 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.513 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-4 x+3 y=\sin \left (t \right ) \\ -2 x+y^{\prime }+y=-2 \cos \left (t \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.595 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-y=0 \\ -x+y^{\prime }={\mathrm e}^{t}+{\mathrm e}^{-t} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.488 |
|
\[
{}\left [\begin {array}{c} x^{\prime }+2 x+5 y=0 \\ -x+y^{\prime }-2 y=\sin \left (2 t \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.640 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-2 x+2 y^{\prime }=-4 \,{\mathrm e}^{2 t} \\ 2 x^{\prime }-3 x+3 y^{\prime }-y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.520 |
|
\[
{}\left [\begin {array}{c} 3 x^{\prime }+2 x+y^{\prime }-6 y=5 \,{\mathrm e}^{t} \\ 4 x^{\prime }+2 x+y^{\prime }-8 y=5 \,{\mathrm e}^{t}+2 t -3 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.685 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-5 x+3 y=2 \,{\mathrm e}^{3 t} \\ -x+y^{\prime }-y=5 \,{\mathrm e}^{-t} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.542 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-2 x+y=0 \\ x+y^{\prime }-2 y=-5 \,{\mathrm e}^{t} \sin \left (t \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.561 |
|
\[
{}\left [\begin {array}{c} x^{\prime }+4 x+2 y=\frac {2}{{\mathrm e}^{t}-1} \\ 6 x-y^{\prime }+3 y=\frac {3}{{\mathrm e}^{t}-1} \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.070 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-x+y=\sec \left (t \right ) \\ -2 x+y^{\prime }+y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.801 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-x-2 y=16 t \,{\mathrm e}^{t} \\ 2 x-y^{\prime }-2 y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.296 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-2 x+y=5 \,{\mathrm e}^{t} \cos \left (t \right ) \\ x+y^{\prime }-2 y=10 \,{\mathrm e}^{t} \sin \left (t \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.356 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-4 x+3 y=\sin \left (t \right ) \\ 2 x+y^{\prime }-y=2 \cos \left (t \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.291 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-2 x-y=2 \,{\mathrm e}^{t} \\ x-y^{\prime }+2 y=3 \,{\mathrm e}^{4 t} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.237 |
|
\[
{}\left [\begin {array}{c} x^{\prime \prime }+x^{\prime }+y^{\prime }-2 y=40 \,{\mathrm e}^{3 t} \\ x^{\prime }+x-y^{\prime }=36 \,{\mathrm e}^{t} \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.050 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-2 x-y=2 \,{\mathrm e}^{t} \\ y^{\prime }-2 y-4 z=4 \,{\mathrm e}^{2 t} \\ x-z^{\prime }-z=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.247 |
|
\[
{}\left [\begin {array}{c} x^{\prime \prime }+2 x-2 y^{\prime }=0 \\ 3 x^{\prime }+y^{\prime \prime }-8 y=240 \,{\mathrm e}^{t} \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.051 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-x-2 y=0 \\ x-y^{\prime }=15 \cos \left (t \right ) \operatorname {Heaviside}\left (t -\pi \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.399 |
|
\[
{}\left [\begin {array}{c} x^{\prime }-x+y=2 \sin \left (t \right ) \left (1-\operatorname {Heaviside}\left (t -\pi \right )\right ) \\ 2 x-y^{\prime }-y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.481 |
|
\[
{}\left [\begin {array}{c} 2 x^{\prime }+x-5 y^{\prime }-4 y=28 \,{\mathrm e}^{t} \operatorname {Heaviside}\left (t -2\right ) \\ 3 x^{\prime }-2 x-4 y^{\prime }+y=0 \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.460 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-x_{2} \\ x_{2}^{\prime }=-4 x_{1}+x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.418 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-3 x_{2} \\ x_{2}^{\prime }=3 x_{1}+x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.458 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=5 x_{1}+3 x_{2} \\ x_{2}^{\prime }=-3 x_{1}-x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.521 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}-x_{2}+x_{3} \\ x_{2}^{\prime }=x_{1}+2 x_{2}-x_{3} \\ x_{3}^{\prime }=x_{1}-x_{2}+2 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.446 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=3 x_{1}-x_{2}+x_{3} \\ x_{2}^{\prime }=x_{1}+x_{2}+x_{3} \\ x_{3}^{\prime }=4 x_{1}-x_{2}+4 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.491 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}+x_{2} \\ x_{2}^{\prime }=x_{1}+3 x_{2}-x_{3} \\ x_{3}^{\prime }=-x_{1}+2 x_{2}+3 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.741 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=3 x_{1}-2 x_{2}-x_{3} \\ x_{2}^{\prime }=3 x_{1}-4 x_{2}-3 x_{3} \\ x_{3}^{\prime }=2 x_{1}-4 x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.490 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-x_{2}+x_{3} \\ x_{2}^{\prime }=x_{1}+x_{2}-x_{3} \\ x_{3}^{\prime }=-2 x_{2}+2 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.465 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=-x_{1}+x_{2}-2 x_{3} \\ x_{2}^{\prime }=4 x_{1}+x_{2} \\ x_{3}^{\prime }=2 x_{1}+x_{2}-x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.461 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}+x_{2}+26 \sin \left (t \right ) \\ x_{2}^{\prime }=3 x_{1}+4 x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.581 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=-x_{1}+8 x_{2}+9 t \\ x_{2}^{\prime }=x_{1}+x_{2}+3 \,{\mathrm e}^{-t} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.543 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=-x_{1}+2 x_{2} \\ x_{2}^{\prime }=-3 x_{1}+4 x_{2}+\frac {{\mathrm e}^{3 t}}{1+{\mathrm e}^{2 t}} \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.070 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=-4 x_{1}-2 x_{2}+\frac {2}{{\mathrm e}^{t}-1} \\ x_{2}^{\prime }=6 x_{1}+3 x_{2}-\frac {3}{{\mathrm e}^{t}-1} \end {array}\right ]
\] |
system_of_ODEs |
✗ |
0.070 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}+x_{2}+{\mathrm e}^{2 t} \\ x_{2}^{\prime }=-2 x_{1}+3 x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.628 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=-x_{1}-5 x_{2} \\ x_{2}^{\prime }=x_{1}+x_{2}+\frac {4}{\sin \left (2 t \right )} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.964 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}+x_{2}+27 t \\ x_{2}^{\prime }=-x_{1}+4 x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.452 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=3 x_{1}-x_{2}+{\mathrm e}^{t} \\ x_{2}^{\prime }=4 x_{1}-x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.477 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=3 x_{1}-2 x_{2} \\ x_{2}^{\prime }=2 x_{1}-x_{2}+35 \,{\mathrm e}^{t} t^{{3}/{2}} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.506 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-x_{2}+x_{3} \\ x_{2}^{\prime }=x_{1}+x_{2}-x_{3}+6 \,{\mathrm e}^{-t} \\ x_{3}^{\prime }=2 x_{1}-x_{2} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.673 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-2 x_{2}-x_{3} \\ x_{2}^{\prime }=-x_{1}+x_{2}+x_{3}+12 t \\ x_{3}^{\prime }=x_{1}-x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.753 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=-3 x_{1}+4 x_{2}-2 x_{3}+{\mathrm e}^{t} \\ x_{2}^{\prime }=x_{1}+x_{2} \\ x_{3}^{\prime }=6 x_{1}-6 x_{2}+5 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
111.138 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=x_{1}-x_{2}-x_{3}+4 \,{\mathrm e}^{t} \\ x_{2}^{\prime }=x_{1}+x_{2} \\ x_{3}^{\prime }=3 x_{1}+x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.968 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}-x_{2}+2 x_{3} \\ x_{2}^{\prime }=x_{1}+2 x_{3} \\ x_{3}^{\prime }=-2 x_{1}+x_{2}-x_{3}+4 \sin \left (t \right ) \end {array}\right ]
\] |
system_of_ODEs |
✓ |
1.297 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=4 x_{1}-x_{2}-x_{3}+{\mathrm e}^{3 t} \\ x_{2}^{\prime }=x_{1}+2 x_{2}-x_{3} \\ x_{3}^{\prime }=x_{1}+x_{2}+2 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
1.993 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}-x_{2}-x_{3}+2 \,{\mathrm e}^{2 t} \\ x_{2}^{\prime }=3 x_{1}-2 x_{2}-3 x_{3} \\ x_{3}^{\prime }=-x_{1}+x_{2}+2 x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.563 |
|
\[
{}\left [\begin {array}{c} x_{1}^{\prime }=2 x_{1}-x_{3}+24 t \\ x_{2}^{\prime }=x_{1}-x_{2} \\ x_{3}^{\prime }=3 x_{1}-x_{2}-x_{3} \end {array}\right ]
\] |
system_of_ODEs |
✓ |
0.565 |
|
\[
{}y^{\prime \prime }-x y = 0
\] |
[[_Emden, _Fowler]] |
✓ |
0.465 |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+4 y^{\prime } x +2 y = 0
\] |
[[_2nd_order, _exact, _linear, _homogeneous]] |
✓ |
0.612 |
|
\[
{}y^{\prime \prime }+x y = 0
\] |
[[_Emden, _Fowler]] |
✓ |
0.458 |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }+y = 0
\] |
[_Gegenbauer] |
✓ |
0.552 |
|
\[
{}y^{\prime \prime }-2 x^{2} y = 0
\] |
[[_Emden, _Fowler]] |
✓ |
0.458 |
|
\[
{}y^{\prime \prime }-2 x^{2} y^{\prime }+x y = 0
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
0.566 |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+\left (4 x -1\right ) y^{\prime }+2 y = 0
\] |
[[_2nd_order, _exact, _linear, _homogeneous]] |
✓ |
0.685 |
|
\[
{}y^{\prime \prime }+\left (\cos \left (x \right )+1\right ) y = 0
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
0.654 |
|
\[
{}y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 0
\] |
[[_2nd_order, _exact, _linear, _homogeneous]] |
✓ |
0.839 |
|
\[
{}x y^{\prime \prime }+y^{\prime }-x y = 0
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
0.613 |
|
\[
{}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }+k y = 0
\] |
[_Laguerre] |
✓ |
0.921 |
|
\[
{}x^{2} y^{\prime \prime }+\left (-2 x^{2}+x \right ) y^{\prime }-x y = 0
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
0.783 |
|
\[
{}x^{2} y^{\prime \prime }-\left (x^{2}+2 x \right ) y^{\prime }+2 y = 0
\] |
[[_2nd_order, _with_linear_symmetries]] |
✓ |
1.265 |
|